IMPROVING THE METHODOLOGY OF DEVELOPING INDEPENDENT THINKING OF PRESCHOOL CHILDREN - Kenjayeva Dildora Terkashevna; Muhammadiyeva Durdona Odil qizi (American Journals, 2024)
This article describes the ideas put forward in the national - spiritual heritage of Eastern thinkers in the cultivation of independent thinking of preschool children. Getting used to rapid changes in the cultivation of independent thinking of preschool children, being able to skillfully apply vital activity, as well as acquired knowledge in solving existing problems, be able to independently and critically think, be able to understand the essence of real existence and emerging problems, seek ways to eliminate them using modern technologies, find effective ways to apply the acquired knowledge in, it is considered important to be able to use information technologies effectively in time and be able to apply them.
Keywords: Acmeolia, preschool education, independent thinking, form, method, medium.